Reconciling Trade and Climate Policies - Nicole A. Mathys; Jaime de Melo (Fondation pour les études et recherches sur le développement international (FERDI), 2012)
The outcome of the 15th conference of the Parties to the UNFCCC in Copenhagen showed a shift from a top-down approach with a collective target favoring environmental objectives to a bottom-up accord favoring political feasibility. There is no meaningful binding agreement in sight, also because the global climate regime and the global trade policy regime appear to be on a collision course. Following a review of the challenges ahead, the paper argues that trade will have a second-order contribution to world-wide CO2 emissions. Evidence shows increasing carbon transfers through trade, but the magnitude of carbon leakage effects may be less than feared in some circles.
Keywords: F18; Q54; Q56; 330